2016
DOI: 10.1124/dmd.115.068536
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril Is Selectively Activated by Carboxylesterase 1 (CES1) in the Liver and the Activation Is Affected by CES1 Genetic Variation

Abstract: Sacubitril was recently approved by the Food and Drug Administration for use in combination with valsartan for the treatment of patients with heart failure with reduced ejection fraction. As a prodrug, sacubitril must be metabolized (hydrolyzed) to its active metabolite sacubitrilat (LBQ657) to exert its intended therapeutic effects. Thus, understanding the determinants of sacubitril activation will lead to the improvement of sacubitril pharmacotherapy. The objective of this study was to identify the enzyme(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 28 publications
(44 reference statements)
1
54
0
Order By: Relevance
“…LCZ696 is rapidly absorbed following oral administration, with peak plasma concentrations of sacubitril, LBQ657, and valsartan observed within a median time of 0.5-4.0 h [9]. Sacubitril is almost completely metabolized by hepatic carboxylesterase 1 (CES-1) but not CES-2, to the active metabolite LBQ657 [10]. This is reflected in minimal recovery of sacubitril in urine and feces (\3 %).…”
Section: Introductionmentioning
confidence: 97%
“…LCZ696 is rapidly absorbed following oral administration, with peak plasma concentrations of sacubitril, LBQ657, and valsartan observed within a median time of 0.5-4.0 h [9]. Sacubitril is almost completely metabolized by hepatic carboxylesterase 1 (CES-1) but not CES-2, to the active metabolite LBQ657 [10]. This is reflected in minimal recovery of sacubitril in urine and feces (\3 %).…”
Section: Introductionmentioning
confidence: 97%
“…Sacubitril is an inactive prodrug and is rapidly hydrolyzed by carboxyl esterases (CES) to form sacubitrilat (also reported as LBQ657), the active neprilysin inhibitor. It was reported that CES-1 but not CES-2 is involved in this conversion, while the role of other CES polymorphs is unknown [2]. Simultaneous inhibition of neprilysin and angiotensin II type-1 (AT1) receptor with LCZ696 showed superior benefits over enalapril in reducing the CV deaths and HF hospitalizations (primary composite endpoint) in the PARADIGM-HF trial in patients with HFrEF [3].…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylesterase 1 is a serine esterase, responsible for the hydrolysis of ester-and amide-bond-containing substrates, including xenobiotics and drugs. Most of ACE inhibitors and sacubitril are ester pro-drugs that are hydrolyzed to their active metabolites just by CES1 [30]. Low CES1 activity-variant carriers may have worse therapeutic response to ACE inhibitors [31].…”
Section: Renal Angiotensin Converting Enzyme (Ace) and Angiotensin IImentioning
confidence: 99%